1995
DOI: 10.3758/bf03203615
|View full text |Cite
|
Sign up to set email alerts
|

Networked simulations: New paradigms for team performance research

Abstract: The prevalence of the use of teams in a variety of occupations and environments has increased the importance of investigating the processes involved in their performance. However, in the past, there have been few methodologies available for the investigation of team performance. The present manuscript attempts to contribute to this area of research by describing the rationale underlying the use of computer-based simulations in research on team performance. This is followed by a review of the networked simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…The prevalence of teams and team-based organizations has made the effectiveness of teams a "vitally important issue". 116 A decade ago, CannonBowers et al 117 concluded from a review of team literature that the import and potential of teams warranted "creative, innovative theoretical and methodological approaches to the study of their design and effectiveness." Yet, the data base in team performance remains small due to methodological challenges in studying teams.…”
Section: Groups and Teams At Workmentioning
confidence: 99%
“…The prevalence of teams and team-based organizations has made the effectiveness of teams a "vitally important issue". 116 A decade ago, CannonBowers et al 117 concluded from a review of team literature that the import and potential of teams warranted "creative, innovative theoretical and methodological approaches to the study of their design and effectiveness." Yet, the data base in team performance remains small due to methodological challenges in studying teams.…”
Section: Groups and Teams At Workmentioning
confidence: 99%
“…On Navy ships, air defense is done in the Combat Information Center (CIC), which contains consoles for activating weapon systems, configuring sensor systems, displaying contact tracks, and communicating with other ships and aircraft. Methodology for modeling such teams has become increasingly sophisticated in recent years (Weaver et al 1995). Figure 1 gives the organization of the 11-person CIC air-defense team on the AEGIS cruiser serving as the Air-Defense Commander for the battle group forces.…”
Section: Introductionmentioning
confidence: 99%
“…Since judgments and decisions in these tasks are rule based and become routine, few higher level, nonroutine, problem-solving processes are demanded. Weaver et al (1995) already noted that, although these simulations appear quite dynamic, in reality they do not allow for much complexity, since the actions required from the team members are repetitive in nature and their roles are too well defined. Consequently, these low-fidelity simulations do not fully satisfy the mentioned team research needs, since these needs also pertain to higher level, complex problem-solving aspects of team performance (cf.…”
mentioning
confidence: 99%
“…A more recent approach that is positioned between these two ends is the use of low-fidelity simulations: networked multiplayer computer games that reflect reality to a certain degree, but still offer control (Weaver, Bowers, Salas, & Cannon-Bowers, 1995). The past quarter century produced a wealth of low-fidelity networked computer simulations.…”
mentioning
confidence: 99%
See 1 more Smart Citation